2020
DOI: 10.1037/vio0000252
|View full text |Cite
|
Sign up to set email alerts
|

Sexual violence, stalking, and intimate partner violence by sexual orientation, United States.

Abstract: Objectives:The objective of this study is to assess the prevalence of sexual violence, stalking, and intimate partner violence (IPV) across sexual orientation groups among U.S. adults. Method:From 2010 to 2012, national probability samples (n = 41,174) of English-or Spanishspeaking noninstitutionalized U.S. adults were interviewed to assess the prevalence of violence and injury as part of the National Intimate Partner and Sexual Violence Survey. National estimates across sexual orientation groups were compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
98
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(110 citation statements)
references
References 40 publications
7
98
1
4
Order By: Relevance
“…In general, SV and IPPV were more common experiences for LGBTQ youth entering college, compared with non-LGBTQ youth-a similar finding to prior research in adults and adolescents (e.g., Bender and Lauritsen 2021;Chen et al 2020;Langenderfer-Magruder et al 2016;Martin-Storey 2015;Saewyc et al 2006). Results indicated that 57% of LGBTQ youth in the current sample experienced some form of SV, and 48% experienced IPPV, since the age of 14.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In general, SV and IPPV were more common experiences for LGBTQ youth entering college, compared with non-LGBTQ youth-a similar finding to prior research in adults and adolescents (e.g., Bender and Lauritsen 2021;Chen et al 2020;Langenderfer-Magruder et al 2016;Martin-Storey 2015;Saewyc et al 2006). Results indicated that 57% of LGBTQ youth in the current sample experienced some form of SV, and 48% experienced IPPV, since the age of 14.…”
Section: Discussionsupporting
confidence: 83%
“…transgender, and queer (LGBTQ) people in the United States are at greater risk of experiencing sexual victimization (SV) and intimate partner physical violence (IPPV) than their heterosexual and cisgender peers (e.g., Bender and Lauritsen 2021;Chen et al 2020;Johnson et al 2016;Langenderfer-Magruder et al 2016;Martin-Storey 2015); such victimization experiences are associated with health-related consequences (Reuter et al 2017;Whitton et al 2019b). Although prevalence rates vary considerably across studies (Decker et al 2018;Edwards et al 2015;Peitzmeier et al 2020;Wirtz et al 2020), recent estimates suggest that *46% of lesbian women, 69% of bisexual women, 38% of gay men, and 39% of bisexual men are sexually victimized within their lifetime, whereas lifetime prevalence rates of IPPV are 40%, 50%, 30%, and 32%, respectively (Chen et al 2020). Additionally, 21% of gay/lesbian and 29% of bisexual/pansexual college students experience SV, whereas 60% of sexual minority college students experience IPPV while in college (Gillum 2017;Kammer-Kerwick et al 2019).…”
mentioning
confidence: 99%
“…This compares with 26% of gay men and 37% of bisexual men who have experienced IPV that covers a range of abusive experiences (Breiding et al, 2013). In a U.S. probability sample, gay and bisexual male participants reported higher rates of stalking than heterosexual men (recorded as 11.4% for gay men, 6.9% for bisexual men vs. 5.2% for heterosexual men; Chen et al, 2020). Across eight U.S. educational institutions, 53.1% of sexual minority students experienced unwanted pursuit, significantly higher than the heterosexual participants (36.0%; Edwards et al, 2015).…”
Section: Resultsmentioning
confidence: 97%
“…Stalking was also identified as a common component of IPV that is more prevalent in sexual minority relationships than in heterosexual relationships. Studies largely recruit heterosexual samples and seldom take stock of sexual minority populations (Chen et al, 2020; Langenderfer-Magruder et al, 2020; Sheridan et al, 2019; Strand & McEwan, 2011), resulting in a scarcity of empirical data in the stalking literature base to expand the issue to gay and bisexual men (Black et al, 2011; Pathé et al, 2000). While many IPV studies exclude experiences of stalking, one study that examined both phenomena indicated that 66.27% of gay men and 60.38% of bisexual men reported victimization of intimate stalking as a form of IPV ( N =136; Dickerson-Amaya & Coston, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…This trend is ethically concerning in terms of making sexual minority individuals invisible within this body of research. Additionally, some research suggests that among sexual minority individuals, those who identify as bisexual (who could presumably be enrolled in studies of male violence against women) experience the highest rates of violence (Chen, Walters, Gilbert, & Patel, 2020 ) compared to individuals who are heterosexual, gay, or lesbian. Thus, we are unable to draw conclusions about the role of social support for a particularly vulnerable group.…”
Section: Discussionmentioning
confidence: 99%